PENGALAMAN WARGA BELAJAR PAKET C DALAM INTERNALISASI 7 KEBIASAAN HEBAT DI PKBM RUMAH KESADARAN - Ramadhanti, Adinda; Darmawan, Dadan; Maysara, Siska Resti; Umronih Y, Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the experiences of Package C students in internalizing the 7 Great Habits program at the Rumah Community Learning Center (PKBM). The study used a qualitative approach with descriptive methods to understand the experiences, understanding, and behavioral changes of students after participating in the habituation program. The research subjects were Package C students who actively participated in the 7 Great Habits program. Data collection techniques were carried out through observation, interviews, and documentation. The results showed that the 7 Great Habits program was implemented through various habituation activities, such as Dhuha prayer, charity, memorization of short surahs, greetings and greetings, tadarus, prayers and affirmations before learning, and congregational Dzuhur prayer. Students understood that the program aimed to shape religious character, discipline, and self-awareness. This program also had a positive impact on changes in student behavior, such as increased awareness of worship, more diligent reading of the Qur'an, and starting to maintain attitudes and behavior in daily life. However, the implementation of these habits has not been fully consistent outside the PKBM environment due to a lack of supervision and environmental support. Therefore, successful character formation through habituation requires ongoing support from educational institutions, families, and the social environment so that the positive values that have been implemented can be consistently implemented in daily life.